Pendekatan Ilat Hukum dalam Penalaran Fikih - Rahmat, Rahmat (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2018)
This journal is written to analyze fqh reasoning by illat of law, requirements and implementation in the process of independent reasoning (ijtihad). The writing of this journal refers to the explanation of the islamic jurists on analogical reasoning (Qiyas) or the analogy among issues in fqh, specifcally the one which is categorized as rational issues (ma'qul al-ma'na). In conclusion, reasoning in fqh might be conducted by illat of law methodology and requirements in the characteristics, such as clearance and unambiguousity, constant and unchangeable, universal or limitless in law itself.